Android Application for Electronic Prescription (Wasfaty) - Alqadi, Amira Khayri; Hawedi, Hadya S.; Albahbah, Aya Muhammad; Ben Masoud, Hawa Emhemed; Alfotaisy, Noor Muftah (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
In an important step to take advantage of technology in the development of health care services, and in an important development in how to write a medical prescription, and the emergence of many technologies, websites and electronic applications in this field, as it was difficult to read the paper prescription, the idea of creating an electronic application for the electronic medical prescription appeared, to enable the doctor to write the prescription electronically in a clear manner, and to facilitate the process of reading the medicine to the pharmacist and dispensing the correct medicine, and to save the time that the pharmacist may take to quickly read the prescription written in the doctor’s handwriting, as a result, an electronic prescription application was created to enable the doctor to write a correct and accurate prescription, and to enable the patient to store his personal and medical data and to obtain instructions and instructions for the medication prescribed to him and to refer to the prescription when needed, and to enable the pharmacist to read the prescription correctly and quickly and to dispense the correct medication to the patient after that. In an important step to take advantage of technology in the development of health care services, and in an important development in how to write a medical prescription, and the emergence of many technologies, websites and electronic applications in this field, as it was difficult to read the paper prescription, the idea of creating an electronic application for the electronic medical prescription appeared, to enable the doctor to write the prescription electronically in a clear manner, and to facilitate the process of reading the medicine to the pharmacist and dispensing the correct medicine, and to save the time that the pharmacist may take to quickly read the prescription written in the doctor’s handwriting, as a result, an electronic prescription application was created to enable the doctor to write a correct and accurate prescription, and to enable the patient to store his personal and medical data and to obtain instructions for the medication prescribed to him and to refer to the prescription when needed, and to enable the pharmacist to read the prescription correctly and quickly and to dispense the correct medication to the patient after that.
Keywords: Android; Electronic application; Prescription; Wasfaty